The South China Sea maritime dispute : political, legal and regional perspectives - Buszynski, Leszek; Roberts, Christopher B.; Buszynski, Leszek (New York : Routledge, 2015)
'The South China Sea, a major strategic waterway for trade to Japan and Korea, has been the focus of a maritime dispute for six decades, with competing claims from China, Vietnam, the Philippines, Indonesia and Brunei. Recently China has become more assertive in pressing its claims - harassing Vietnamese and Philippine fishing boats, publicising its claims more prominently, and threatening to board ships around the islands claimed by China. All of this is unsettling, with the United States supporting the Philippines, and developing security ties with Vietnam. This book examines the conflict potential of the current dispute, discusses the views of the main claimants and the United States, and assesses the prospects for resolution'--
1. The origins and development of the South China Sea maritime dispute / Leszek Buszynski -- 2. Adrift on complex waters : geographical, geopolitical and legal dimensions to the South China Sea disputes / Clive Schofield -- 3. The 1982 UN Convention on the law of the sea and its relevance to maritime disputes in the South China Sea / Donald R. Rothwell -- 4. China's South China Sea policy : evolution, claims and challenge / Jian Zhang -- 5. Vietnam's evolving claims / Do Thanh Hai -- 6. The 2012 Scarborough Shoal stand-off : from stalemate to escalation of the South China Sea dispute? / Renato Cruz De Castro -- 7. ASEAN : the challenge of unity in diversity / Christopher B. Roberts -- 8. The US rebalance to Asia and the South China Sea disputes / Ralf Emmers -- 9. Australia's interests in the South China Sea / Michael Wesley -- 10. The South China Sea as a'crisis' / Brendan Taylor -- 11. The South China Sea : stabilisation and resolution / Leszek Buszynski and Christopher B. Roberts.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: South China Sea -- International status